Differences in oculomotor behaviour between elite athletes from visually and non-visually oriented sports - Morgan, S.; Patterson, J. (International Journal of Sport Psychology, 2009)
The oculomotor characteristics of elite athletes between differing sports have been largely overlooked. Instead the research focus has been dedicated to describing perceptual differences between elite and novice athletes within a given sport. Our aim was to compare and contrast the oculomotor attributes of elite groups of netball players, swimmers, and cyclists.We conducted a series of visual search experiments using a novel task that was unfamiliar to their domain of expertise. These sports were selected on the assumption they may entail differing visual processing demands, and that the adaptive visual search behaviour of each on an unfamiliar task may be different. The results revealed that the elite netball players generated saccadic eye movements more frequently than both the elite swimmers and the elite cyclists. Further, the mean amplitudes and mean peak velocities of saccades in the netball group were significantly higher than in the other groups. Importantly, analysis of the saccade main sequence showed that the netball group exhibited higher peak velocities for equidistant saccades compared to the other groups. These results suggest that there may be underlying differences in both the oculomotor capability and adaptive search behaviour of elite athletes from different sport backgrounds.